Understanding the Relationship between Rainstorm-Related Experiences and PTSD among Chinese Adolescents after Rainstorm Disaster: The Roles of Rumination and Social Support - Zhen, Rui; Quan, Lijuan; Yao, Benxian; Zhou, Xiao (Frontiers in Psychology, 2016)
It has been documented that posttraumatic stress disorder (PTSD) was prevalent among adolescents following natural disasters, and the trauma experiences was a critical risk factor for PTSD. Nevertheless, the underlying process of adolescents’ PTSD remains unclear. Theoretical studies indicate that rumination may be a mediating factor between trauma experiences and PTSD, and social support may moderate the relations of trauma experiences and rumination to PTSD, but fewer studies examine these assumptions. Thus, this study aimed to assess the mediating role of rumination and the moderating role of social support in the relationship between rainstorm-related experiences and PTSD among adolescents following rainstorm in China. 951 middle school students were investigated by self-report questionnaires, and structural equation model was conducted to examine the potential moderated mediation effect. The results showed that rainstorm-related experiences had a direct and positive effect on PTSD, and it could also indirectly affect PTSD by rumination. Moreover, social support could buffer the direct effect of rainstorm-related experiences on PTSD, but not the effect of rumination on PTSD. Finally, implications for clinical practice and research were discussed along with study limitations.